Residual stresses in (Zr,Hf)N films (up to 11.9 at.% Hf) measured by X-ray diffraction using experimentally calculated XECs - SARIOĞLU, CEVAT (ELSEVIER SCIENCE SA, 2005)
In the present work, the residual stresses of (Zr,Hf)N films were measured using X-ray diffraction (XRD) fixed incident multiplane technique (FIM) for varying amounts of Hf addition by assuming the film was isotropic and anisotropic (Kronel model). The residual stress values calculated according to isotropic and anisotropic models were almost the same (-6 GPa). Addition up to 11.9 at.% Hf into ZrN films did not affect the level of residual stress. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: thin film; X-ray diffraction; residual stress; coatings; ZrN and HfN; ZIRCONIUM NITRIDE COATINGS; HARD COATINGS; ARC-EVAPORATION; THIN-FILMS; DEPOSITED COATINGS; ELASTIC-CONSTANTS; VACUUM-ARC; MULTICOMPONENT; TIN; PVD